1996
DOI: 10.1007/bf00188479
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic surgery for mature teratoma of the ovary

Abstract: Our findings confirm those of other authors- when performed by experienced surgeons, laparoscopic removal of ovarian mature teratomas is a safe and recommendable alternative to laparotomy. Preoperative diagnosis and intraoperative inspection of the tumor must be as thorough as possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
1
2

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 18 publications
0
5
1
2
Order By: Relevance
“…In fact the mean operative time in our experience (64 min) is similar to that reported by Volz et al [10], who used a similar technique, and by Yuen and Rogers [20] (60 min) and Morgante et al [58] (57 min) for open surgery and by Pardi et al [42] for laparoscopy-assisted vaginal removal, but it was lower than what was reported by other authors for laparotomy [18,21,22] or laparoscopy (table 2), [8,9,12,18,19,20,21,22,26,27,29,33,34,36,37,39,40]. Our mean surgical time is also lower than that reported by Ferrari et al [38] or Wang et al [44] for the direct vaginal approach (81 and 78 min, respectively).…”
Section: Discussioncontrasting
confidence: 46%
See 2 more Smart Citations
“…In fact the mean operative time in our experience (64 min) is similar to that reported by Volz et al [10], who used a similar technique, and by Yuen and Rogers [20] (60 min) and Morgante et al [58] (57 min) for open surgery and by Pardi et al [42] for laparoscopy-assisted vaginal removal, but it was lower than what was reported by other authors for laparotomy [18,21,22] or laparoscopy (table 2), [8,9,12,18,19,20,21,22,26,27,29,33,34,36,37,39,40]. Our mean surgical time is also lower than that reported by Ferrari et al [38] or Wang et al [44] for the direct vaginal approach (81 and 78 min, respectively).…”
Section: Discussioncontrasting
confidence: 46%
“…Most benign teratomas are asymptomatic [4,12,13]. In the present series, teratomas were diagnosed by ultrasound and gynecological examination in 23 asymptomatic patients; only 12 patients reported pelvic pain.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“… 5 – 7 The management of a dermoid cyst therefore depends more on its symptoms and clinical findings than the very small risk of actual malignancy. 8 , 9 A decision can then be made between conservative management, laparoscopic surgery or laparotomy depending upon the patients’ symptoms, age, clinical findings and ultrasonographic features. 10 …”
mentioning
confidence: 99%
“…The rate of rupture during laparoscopy is very high in MCTs. Approximately 54% has been detected ( 21 , 22 , 23 ) . The probability of rupture has been found to be independent of size and location of MCT ( 24 , 25 ) .…”
Section: Discussionmentioning
confidence: 99%